Penguatan Kemandirian Benih Padi Lokal melalui Pelatihan Teknologi Backcross di Desa Sumbersalak, Jember: Program Pengabdian kepada Masyarakat - Sholikhah, Ummi; Ahmad Ilham Tanzil; Wahyu Indra Duwi Fanata; Tri Ratnasari; Yusuf Rachmandhika (Universitas Mataram, 2025)
Strengthening the independence of local rice seeds is a strategic effort to increase agricultural productivity while preserving the sustainability of local varieties. Sumbersalak Village, Ledokombo Sub-district, Jember Regency, has the potential of adaptive local rice, yet the seed quality still needs improvement. This community service program aims to provide training and technical assistance to farmers in applying backcross technology for the improvement of local rice seeds. The implementation methods include socialization, hands-on training in backcrossing, field assistance, as well as evaluation through pretests and posttests. The results showed an increase in participants’ understanding from an average of 30% (pretest) to 94% (posttest) in terms of backcross concepts and techniques. Field practices successfully demonstrated the stages of crossing and line selection, although a small number of participants still required additional guidance in the controlled pollination stage. This activity demonstrates that the transfer of backcross technology can enhance farmers’ capacity to produce high-quality and adaptive local rice seeds, thereby supporting seed self-reliance in Sumbersalak Village.